Digital Marketing Strategies and Consumer Behavior: Analyzing the Effectiveness of Social Media Campaigns - Nawab Akram, (European Economic Letters (EEL), 2024)
This study focuses specifically on social media methods while analysing the efficacy of digital marketing strategies and their influence on consumer behaviour. Businesses are depending more and more on social media platforms in today's quickly changing digital landscape to interact with consumers and build brand loyalty. In order to determine how different advertising strategies, such as social proof, peer recommendations, and personalized content, affect customer purchase decisions, the study assesses these strategies. It also looks at how user-generated content and influencer marketing affect brand perception and encourage interaction. The results show that effective social media marketing techniques not only make it easier to communicate directly with customers, but also build credibility and trust, which boosts sales and raises customer satisfaction. Businesses may engage with their customers in more meaningful and genuine ways by utilizing social media. The report emphasizes how important it is for marketers to use new developments in digital marketing to their advantage and adjust to shifting consumer preferences. A thorough grasp of these dynamic tactics is necessary to create campaigns that connect with target audiences and make an impression. This study emphasizes how important social media is to contemporary marketing and how well it can affect consumer behaviour.